2018
DOI: 10.1145/3173380
|View full text |Cite
|
Sign up to set email alerts
|

Workload Alerts—Using Physiological Measures of Mental Workload to Provide Feedback During Tasks

Abstract: Feedback is valuable for allowing us to improve on tasks. While retrospective feedback can help us improve for next time, feedback "in action" can allow us to improve the outcome of on-going tasks. In this paper, we use data from functional Near InfraRed Spectroscopy to provide participants with feedback about their Mental Workload levels during high-workload tasks. We evaluate the impact of this feedback on task performance and perceived task performance, in comparison to industry standard mid-task self asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…In symbiotic systems, these users' collected data could be shared among all the computational devices connected through the network. Once it detects the operator's need for support (e.g., an extreme level of stress), the system could tailor its interface and functions by implementing real-time adaptive features [7,8]. These concepts were modeled by Gamberini and Spagnolli ([3]; see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In symbiotic systems, these users' collected data could be shared among all the computational devices connected through the network. Once it detects the operator's need for support (e.g., an extreme level of stress), the system could tailor its interface and functions by implementing real-time adaptive features [7,8]. These concepts were modeled by Gamberini and Spagnolli ([3]; see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…To consider the critical aspects of the symbiotic system mentioned above, we needed to identify a reliable construct that could be assessed based on implicit, explicit, and subjective measures [16]. Within the work context [8], the impact of mental workload (MWL) on performance has been analyzed [17][18][19], especially regarding its optimization for users operating in the environment of so-called Industry 4.0 [20].…”
Section: Introductionmentioning
confidence: 99%
“…Another significant use of PFC asymmetry has been early NF experiments, primarily for the treatment of depression (Rosenfeld et al, 1995). PFC asymmetry has been later adopted as a BCI technology taking advantage of the above results, and has been used for affective computing (Mühl and Heylen, 2009) cognitive workload measurement (Fishburn et al, 2014;Peck et al, 2014;Barth et al, 2016;Maior et al, 2020) or assessment of aesthetic response (Karran et al, 2015;Cartocci et al, 2016).…”
Section: Pfc Asymmetry In Neuroscience Researchmentioning
confidence: 99%
“…In our prior work, we have anecdotally observed the difference between participants who enjoy a task, and those that are worried or stressed about achieving them [11], where stressed participants tended to perform worse. It has been suggested that Selye coined the term 'stress' in 1936 [15].…”
Section: Introductionmentioning
confidence: 98%